Current oscillations and intermittent emission near an electrode interface in a hybrid organic-inorganic perovskite single crystal - Hettiarachchi, Chathuranga (2020)
Hybrid organic-inorganic lead perovskites have a great potential in optoelectronic device applications because of their high stability, narrow band emission, and strong luminescence. Single crystals with few defects are the best candidates to disclose a variety of interesting and important properties for light-emitting devices. Here, we investigate a single-crystalline CH3NH3PbBr3 perovskite for its transport and electroluminescence properties. A simple fabrication method was used to obtain a 10 ± 2 μm channel between two gold wire electrodes, which showed bright intermittent electroluminescence near the interface of one wire after cooling down with a constant biasing voltage. The active region of the perovskite single crystal was pristine, well isolated from surroundings through fabrication to the characterization process. Our presented sample provided an ideal condition to study bulk ionic-electronic properties of hybrid halide perovskites. At constant 6 V bias, the current through the sample shows temperature-dependent oscillation with Arrhenius behavior, suggesting a thermally activated process. The light emission from the sample experiences an intermittent emission rate once every 26 ± 6 min. Here, we envisage that the current oscillations and intermittent emission are caused by ion-mediated negative differential resistance and conductive filament formation, respectively. The latter observation inspires future applications of the material from neuromorphic computing to the development of electroluminescence devices.